New species of Spauligodon (Nematoda: Pharyngodonidae) in Xenosaurus platyceps (Squamata: Xenosauridae) from Mexico - Bursey, Charles R.; Goldberg, Stephen R.; Telford, Sam R. (Zootaxa, 2007)
During a helminthological examination of flathead knob-scaled lizards, Xenosaurus platyceps King and Thompson 1968, from Mexico, 4 of 10 were found to harbor 56 (14 male, 42 female) nematodes of an undescribed species of Spauligodon Skrjabin, Schikhobalova and Lagodovskaja, 1960. The lizard family Xenosauridae is composed of two well-differentiated genera: Shinisaurus in southern China and Xenosaurus in Mexico and Guatemala (Pérez-Ramos et al., 2000). Xenosaurus platyceps is a stocky, medium-sized species endemic to the Mexican state of Tamaulipas where it occurs in dry oak and tropical deciduous forests of the Sierra Madre Oriental (Flores-Villela 1993; Flores-Villela and Gerez, 1994). The ecology of X. platyceps has been studied (Lemos-Espinal, 1997), but, to our knowledge, there are no helminthological reports for it.